Hubungan Pengendalian Sistem FIfo dan Kualitas Produk Pada H20 Pool Bar di Hotel Novotel Manado - Veronika Umboh (PolimdoSains, 2019)
This research focuses on H2O Bar in storing fruit raw materials that is still not well controlled yet so that it affects the ineffectiveness of inventory and decreases product quality. Therefore the relationship between FIFO system control and product quality at the H2O bar at Novotel Manado hotels needs to be examined. The research aims to measure how much the FIFO system relates to control product quality at the H2O bar at the Novotel Manado hotel and then analyzes and explains how and why the FIFO system controls and product quality. This study uses quantitative research method, namely data obtained in the form of numbers that can be calculated with primary and secondary data collected by survey, observation and literature study methods. The study concluded that the correlation coefficient or r = 0.625, which means that there is a positive and strong relationship between the FIFO control system and the drinking product quality which means that if the FIFO control system is increased or reduced then the quality of the product will increase / decrease.